A Microwave Imaging Matrix Algorithm Based on Contrast Source. (8th June 2022) - Wang, Meng; Lu, Guizhen; Chen, Junwen
Abstract : A microwave imaging matrix algorithm based on the contrast source is proposed. It is known that the contrast source and the total field change by shifting the position of the incident field. To ensure the constancy of the contrast source, this paper first proposes a novel inversion model based on the contrast source. The excitation source is located at a single fixed position, and the scattering data is obtained by measuring points evenly distributed on multiple circular layers. Secondly, a matrix algorithm based on the contrast source is proposed, which transforms the nonlinear imaging problem into a matrix operation step-by-step without iteration. The numerical simulation results show that the matrix algorithm proposed in this paper has high precision and good performance with complex imaging problems. In addition, the limitation of the proposed algorithm when inversing data with noise is also analyzed.